Kirke og prigrim i "Pilgrim's Progress" - Gregersen, Susanne (Religionsvidenskabeligt Tidsskrift, 1991)
John Bunyan's Pilgrim's Progress has usually been interpreted as a allegorical account of an individual pilgrim's search for salvation and sanctification on his lonely soul-journey, with a superimposed addition of church fellowship in the second part of the story. An interpretation like this loses the depth and complexity of Bunyan's story. Far from being an individual story Pilgrim's Progress describes the relationship and covenant between the individual pilgrim and the visible church of the elect as depicted in the Palace Beautiful. In Palace Beautiful, the history of the individual pilgrim from The City of Destruction to The Celestial City meets the history of God's salvation of his elected people from before creation to the Last Day. If any of these three layers of interpretation is missed out or translated into modern individualism, the whole scope of Bunyan's imaginative universe is reduced and oversimplified.